DIGITAL REVOLUTION: HOW SOCIAL COMMERCE TRANSFORMS ALGERIAN ART CRAFTS - Benaissa Maya Ines; Kassah Laouar Ines (International Journal of Innovative Technologies in Social Science, 2024)
The craft sector, in addition to constituting an invaluable cultural, social and historical heritage, is a leading niche with high added value, which, associated with the power of ICT, is experiencing a major ascent like never before. Social networks are today the most widespread communication media in the world. Having as main vocation to develop the reputation of others, craft enterprises have also taken advantage of these tools to take advantage of the actions and network that each of them offers, this allows them to include handmade items in a strategy of artisanal renewal. The objective of this article is to observe, through a quantitative study with artisans’ entrepreneurs but also Algerian consumers, the impact of social commerce on the motivation and behavioral intention of Algerian consumers towards artisanal products.